Insulina inalável: desenvolvimento de dispositivo tecnológico - Matos, Igor Leonardo Santos (2024)
Introduction: Diabetes is a chronic disease with a growing impact on global public health, with projections indicating that by 2045, 783 million people will be living with the condition. Effective glycemic control is essential to prevent complications, but treatment adherence faces challenges, especially among patients using injectable insulin, which is often associated with discomfort and negative perceptions. In this context, inhaled insulin emerges as a less invasive and more practical alternative. Although devices like Exubera® and Afrezza® have pioneered this field, they still face limitations in acceptance and adverse effects, such as coughing and throat irritation, possibly due to suboptimal inhaler designs. Objective: To develop an optimized dry powder inhaler (DPI) for the effective and uniform administration of insulin to diabetic patients. Methods: A literature review on DPIs was conducted to identify advancements and limitations. The Venturi effect was applied to the design to accelerate airflow through a narrow channel, promoting effective insulin powder atomization and facilitating absorption. The modeling was performed using Fusion 360® software, enabling the creation of a 3D prototype and visualization of structural mechanism details. Device development: The device was designed to accommodate patients with respiratory and motor difficulties. The dimensions of the channel and airflow velocity were adjusted to achieve a rate of 64 liters/hour, ensuring efficient dispersion of particles ranging from 2 to 5 micrometers. Key components include an enlarged suction mouthpiece and an adjustable Venturi shaft to facilitate administration. Results and Discussion: The inhaler was designed to optimize the administration of inhalable insulin, ensuring uniform particle dispersion between 2 and 5 micrometers, with good ergonomics, medium intrinsic resistance, and reduced costs. The device offers technical and commercial advantages, including improved dispersion, reduced respiratory tract irritation, and protection through a utility model patent. Conclusion: Diabetes represents a costly challenge for healthcare systems and patients. Inhalable insulin devices have the potential to improve treatment adherence, despite existing shortcomings. Thus, a 3D model of an optimized inhaler for insulin use was developed based on the Venturi effect and subsequently submitted for a utility model patent at the INPI.